Effects of Nursery Tray and Transplanting Methods on Rice Yield. (1st January 2018) - He, H.; You, C.; Wu, H.; Zhu, D.; Yang, R.; He, Q.; Xu, L.; Gui, W.; Wu, L.
Abstract : Core Ideas: The grain yield was highest in the Pot‐S treatment, followed by the Pot‐flat‐S treatment and the Flat‐S treatment. Insufficient sink size (number of effective panicles multiplied by number of spikelets per panicle) is the key factor in the grain yield reduction in the Flat‐S treatment. The spatial distribution characteristics of the first and second leaves were crucial for the high yield formation of mechanically transplanted rice. The objective of this 2‐yr field experiment was to compare the performance of three rice ( Oryza sativa L.) cultivars grown in three different nursery trays and mechanically transplanted using compatible machinery. The three treatments were a blanket‐type nursery tray (Flat‐S treatment), a bowl‐type nursery tray (Pot‐S treatment), and a pot‐style/blanket‐type nursery tray (Pot‐flat‐S treatment). The net photosynthetic rate, leaf area index, dry matter accumulation, and matter translocation from the sheath at flowering to the kernel were significantly higher in the Pot‐S treatment than in other two treatments ( p < 0.05). The highest grain yield was in the Pot‐S treatment (9.15–11.81 × 10 3 kg ha –1 ), followed by the Pot‐flat‐S treatment (8.84–10.62 × 10 3 kg ha –1 ), and then the Flat‐S treatment (8.3–9.78 × 10 3 kg ha –1 ). Low yields were attributed mainly to weak sink characteristics. The relative heights of the top three leaves on the plant were higher in the Pot‐S treatment than in the other two treatments, and there was more space between adjacent leaves at the top of the canopy in the Pot‐S treatment than in the other two treatments. The flag leaf area, the height difference between the first and third leaves (HDfirst‐third ) and between the second and third leaves (HDsecond‐third ), the relative height of the first leaf, and the droop angle of the first leaf significantly affected the source and sink traits. Moreover, HDfirst‐second and HDfirst‐third significantly and directly affected grain yield. Thus, the HDs of the top three leaves were crucial for high yields of mechanically transplanted rice.